Auditoría de gestión a los procesos de producción de la panificadora “La Vienesa” Riobamba, periodo I semestre 2022 - Logroño Caceres, Anthony Fabian (2024)
ABSTRACT: The objective of the research work was to examine the management auditory of the production processes carried out at the bakery "La Vienesa" regarding the first semester of the 2022 period. The study of the research project is descriptive with a quantitative approach, a non-experimental design was used since it implied the recording of the observed results without having manipulated any variable, the data collected were extracted by means of the questionnaire instrument to execute the surveys that were applied to the examined population conformed by 24 employees from the production area. The results revealed that the internal control has a medium level of trustworthiness, due to the absence of supervision, measurement and evaluation to the stages that are executed in the manufacturing area, which allowed to conclude that the decrease in the production performance was due to the deficient management in the production area.